Proposal of an organizational culture model for innovation - Felizzola Cruz, Yadira Milena; Anzola Morales, Olga Lucía (Cuadernos de Administración, 2017)
Based on a case study from a company within the Engineering sector with presence in Colombia an organizational culture model for innovation is proposed. Organizational culture is important for innovation since the capacity to innovate demands a taste for risk and willingness to carry out entrepreneurship, which become stronger by an appropriate climate and environment that motivates individuals to create and develop new ideas. The proposal set forth herein parts from diagnosis of the organizational culture present within a company, which allows to identify the existing breach between the basis organizational culture and organizational culture for innovation. The breaches to act upon are identified, with the purpose of reaching an organizational culture of innovative characteristics, and some recommendations for its intervention are proposed. The assumptions on organizational culture typology are confirmed, and the importance of integrating creativity, taste for risk and willingness for entrepreneurship within organizational culture for innovation is highlighted.